SYNTAX AND ITS MAIN UNITS. TRADITIONAL AND COGNITIVE APPROACHES IN SYNTAX ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an in-depth examination of syntax, the branch of linguistics that studies how words combine to form phrases and sentences. It outlines the main syntactic units—words, phrases, clauses, and sentences—and explains how these elements interact to convey meaning in language. The article then contrasts traditional and cognitive approaches to syntax. Traditional syntax emphasizes rule-based structures and formal hierarchies, focusing on sentence diagrams and fixed grammatical categories. In contrast, cognitive approaches view syntax as a reflection of human cognition, influenced by experience, context, and meaning. Key concepts such as Construction Grammar and embodied cognition demonstrate how cognitive linguistics connects syntax with conceptual and cultural aspects of language use. Through comparing both approaches, the article highlights how syntax operates not only as a structural system but also as a flexible, meaningful component of human communication. This dual perspective allows for a richer understanding of syntax's role in language and links it to broader cognitive and cultural processes.